Research Paper on Data Security Through Speech Recognition In Cloud Computing - Sharma, Nisha; kishor, Er. Amit (International Journal of Computer Sciences and Engineering, 2018)
Affects like lower cost, boom throughput, availability however it additionally Information and telecommunication generation (ICT) has through deep into the person lives and is impacting person life fashion in one-of-a-kind components. The quick increase in ICT has commenced upgrade in computing gadget and computing expertise. Presently cloud computing is one of the extreme promoted transformation. It has various effective have positive safety problems that have to be treated delicately. There are various procedures that may be used to conquer this foremost hassle. Here this paper will research biometric authentication for data safety in cloud computing, it’s numerous techniques and the way they're useful in decreasing the security warning. It gives an expansive and organized evaluation of biometric authentication for boosting cloud protection.